Curbing the Social Menace of Modern Slavery in Edo State, Nigeria: The Law and Criminal Justice System, a Panacea? - Obarisiagbon, Barr. Emmanuel Imuetinyan; Ijegbai, Robert Uwaifo (European Scientific Journal, ESJ, 2019)
Migration and modern slavery are global problems which affect developed and developing nations alike. However, the magnitude of the menace varies; with less developed countries facing more of the challenges. There are many reasons responsible for the increase in the rate of migration and the attendant modern slavery which are replete in literature. Today, some 30 million people worldwide live in slavery and yet slavery is strictly prohibited by both Nigerian and international laws (Global slavery index, 2016). Why is there such a gap between law and practice? What can be done to improve the contribution of national law and criminal justice norms and institution towards the eradication of modern slavery? Unfortunately, little or no work has been done to indicate the relevance of law and criminal justice as disposing factors in migration and modern slavery in Nigeria. These are some of the key issues which this paper seeks to address. The study revealed that not only was the public unaware of the existing laws against modern slavery, they were also unanimous in their views that even if these laws existed, they were not effective, as the criminal justice system has not impacted positively on the issue under study. Consequently, the study suggests that the government, non-governmental organizations and media outfits should collaborate in ensuring that the existence of the law on modern slavery is made known to the general public. In addition, the law and the criminal justice should be strengthened in order to make it more effective.